2017
DOI: 10.1590/0001-3765201720160117
|View full text |Cite
|
Sign up to set email alerts
|

Estimated evolution of total pollutant gas emissions associated with vehicle activity in the Metropolitan Region of Porto Alegre until 2030

Abstract: In recent years, the majority of economic sectors in Brazil have gone through processes of development and transformation. These processes have led to increases in environmental pollution of all kinds; air pollution being one of the most adverse. The Brazilian transportation sector, which heavily affects the air quality, experienced a significant increase in its vehicle fleet thus provoking larger emissions of pollutant gases, mainly in regions with high population density such as the Metropolitan Region of Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A more comprehensive description can be found in a Chovert and Alonso (2017) research where energy consumption, production, and extraction of resources are the main functions for LEAP and it can be also conducted in all the sectors of an economy. AlSabbagh, et al (2015) concluded that LEAP is user-friendly, can be modeled with limited data, and does not require substantial expertise to develop models.…”
Section: Letreture Reviewsmentioning
confidence: 99%
“…A more comprehensive description can be found in a Chovert and Alonso (2017) research where energy consumption, production, and extraction of resources are the main functions for LEAP and it can be also conducted in all the sectors of an economy. AlSabbagh, et al (2015) concluded that LEAP is user-friendly, can be modeled with limited data, and does not require substantial expertise to develop models.…”
Section: Letreture Reviewsmentioning
confidence: 99%